(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article investigates how module-based education enhances philology students’ monologue speech abilities at the B2 level. Breaking down the complicated skill of delivering monologue speech into smaller modules allows students to focus on specific components of language creation and delivery. The study looks at how this strategy improves students’ pronunciation, fluency, vocabulary, and overall communication skills. The study aims to provide empirical evidence of the benefits of module-based education in improving students’ monologue speech abilities by analyzing quantitative data.